1996
DOI: 10.1103/physrevb.53.1038
|View full text |Cite
|
Sign up to set email alerts
|

Electron effective mass and nonparabolicity inGa0.47In0.53As/In

Abstract: The in-plane effective electron mass (m ʈ ) in narrow Ga 0.47 In 0.53 As/InP quantum wells is strongly dependent on the quantization energy. Cyclotron resonance in a series of quantum wells with well widths down to 15 Å reveals a mass enhancement of up to 50% (m ʈ ϭ0.065m 0 ) over the bulk value of Ga 0.47 In 0.53 As. This effect is caused by the nonparabolicity of the conduction band and wave function penetration into the barrier material. Our experimental findings are in good agreement with calculations perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…In thin GaAs/AlAs QWs, it has been shown that the effective electron masses increase with decreasing well width. 16 For all samples, the energy dependency of the effective electron mass is calculated using a modified Kane formula, 17,18 …”
Section: A Experiments and Model Calculationsmentioning
confidence: 99%
“…In thin GaAs/AlAs QWs, it has been shown that the effective electron masses increase with decreasing well width. 16 For all samples, the energy dependency of the effective electron mass is calculated using a modified Kane formula, 17,18 …”
Section: A Experiments and Model Calculationsmentioning
confidence: 99%
“…However, the g factor for N = 4 is considerably smaller. Although a part of it can be attributed to the nonparabolicity of the dispersion, 16 the large difference between the two g factors calls for a future study.…”
mentioning
confidence: 96%
“…The size of this enhancement is consistent with that observed in cyclotron resonance measurements on similar structures. 37 There are two small dips in g 2D in samples S and S2 adjacent to the minimum at ν=4; these are fitting artifacts that occur because τ rc is varying rapidly, leading to significant variations across the device and poor fits using the equivalent circuit, as in trace (a) of Figure 6. The fits (and hence values of g 2D ) at ν=4 are more accurate because dτ rc /dH=0…”
Section: Experimental Results: Magnetic Field Dependencementioning
confidence: 99%